Trade, Growth and Technical Change. - Archibugi, D (Cambridge University Press, 1998)
New trade theory, new growth theory and the developing literature on national systems of innovation have combined to produce an explosion of interest over the past two decades around issues of trade, growth and technical change. A similar focus has dominated public policy debates. This book represents a contribution to such debates, focusing as it does on the interconnections between technology, on the one hand, and economic growth and international trade on the other. It identifies and explains the links between these various processes, and explores the effects of technical change on both growth and trade. This book has clear policy relevance: market forces alone are seen to be far from adequate for the efficient generation, transfer and diffusion of innovation, while public policy is identified as playing a key role for a truly innovative economy.